Some conceptual aspect of overcoming anti-detection and investigation of crimes - G.V. Burganova; R.R. Rahmatullin (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper considers the problem of the concept and signs of counteraction to the investigation of crimes. The positions of various legal scholars of the conceptual apparatus of counteraction have been analyzed in detail. The definition of counteraction to the investigation of crimes has been elaborated. The idea has been introduced that the disclosure and investigation of the overwhelming number of crimes is carried out under countering conditions, which makes it difficult to achieve the objectives of the criminal process in specific cases, leads to the situation when many committed illegal acts and omissions remain undetected, and a number of the identified crimes remain undisclosed. Indisputable is the assertion that forensic science plays the main role in shaping the conceptual framework for overcoming counteraction to the detection and investigation of crimes (judicial investigation). At the present stage of research, we can argue about the beginning of the formation of a new forensic doctrine – the doctrine of countering the detection and investigation of crimes (judicial proceedings) and the methods and methods for overcoming them. This vector of development of forensic science is relevant due to practical necessity, the actual state of affairs, as well as the essence of law, which obliges to respond to all the processes occurring in public life.